Axon initial segment Kv1 channels control axonal action potential waveform and synaptic efficacy - Kole, Maarten H P; Letzkus, Johannes J; Stuart, Greg J (Neuron (Cambridge, Mass.), 2007)
Action potentials are binary signals that transmit information via their rate and temporal pattern. In this context, the axon is thought of as a transmission line, devoid of a role in neuronal computation. Here, we show a highly localized role of axonal Kv1 potassium channels in shaping the action potential waveform in the axon initial segment (AIS) of layer 5 pyramidal neurons independent of the soma. Cell-attached recordings revealed a 10-fold increase in Kv1 channel density over the first 50 microm of the AIS. Inactivation of AIS and proximal axonal Kv1 channels, as occurs during slow subthreshold somatodendritic depolarizations, led to a distance-dependent broadening of axonal action potentials, as well as an increase in synaptic strength at proximal axonal terminals. Thus, Kv1 channels are strategically positioned to integrate slow subthreshold signals, providing control of the presynaptic action potential waveform and synaptic coupling in local cortical circuits.